Extracellular loops 2 and 3 of the calcitonin receptor selectively modify agonist binding and efficacy - Dal Maso, Emma (Biochem Pharmacol, 2018)
Class B peptide hormone GPCRs are targets for the treatment of major chronic disease. Peptide ligands of these receptors display biased agonism and this may provide future therapeutic advantage. Recent active structures of the calcitonin (CT) and glucagon-like peptide-1 (GLP-1) receptors reveal distinct engagement of peptides with extracellular loops (ECLs) 2 and 3, and mutagenesis of the GLP-1R has implicated these loops in dynamics of receptor activation. In the current study, we have mutated ECLs 2 and 3 of the human CT receptor (CTR), to interrogate receptor expression, peptide affinity and efficacy. Integration of these data with insights from the CTR and GLP-1R active structures, revealed marked diversity in mechanisms of peptide engagement and receptor activation between the CTR and GLP-1R. While the CTR ECL2 played a key role in conformational propagation linked to Gs/cAMP signalling this was mechanistically distinct from that of GLP-1R ECL2. Moreover, ECL3 was a hotspot for distinct ligand- and pathway-specific effects, and this has implications for the future design of biased agonists of class B GPCRs.